SISTEM INFORMASI DATA KEANGGOTAAN BERBASIS WEB PADA KANTOR KWARDA PRAMUKA PROVINSI JAMBI: System, Information, Scout Membership, Web. - Simorangkir, Lucy; Ozi Aransyah, Ande (JURNAL AKADEMIKA, 2019)
Kwarda Pramuka Office Jambi Province is a scout movement organization in Jambi Province, which has the task of leading and controlling scout movements and scouting activities. But the information system that is used for data service and membership processing is still manual. This study aims to establish a membership data information system so that it is easier to obtain information about membership data services, registration of new members without having to go to the office of Kwarda Pramuka Jambi Province. This system was built based on the web using the Php programming language and MySQL database. Input from this application is activity data, gallery, admin, news, employees, members, and history. While the output is in the form of profiles, member registration and information on activities to be held by the Kwarda Pramuka Jambi Province. The results showed that with the web as a medium of information, the process of processing information data and activity agendas was more easily conveyed to the public such as the Kwartir Branch, Kwartir Branch, Front Cluster and especially Jambi Province Scouts and the general public easily knew some about Kwarda Scout Jambi Province.